(untitled) (Sirte University Journal of Humanities, 2026)
This study examines the impact of Chat GPT as part of AI in education on English homework practices in the EFL context of preparatory schools in Sirte, Libya. It explores preparatory teachers’ perspectives on students’ increasing reliance on Chat GPT for completing assignments. Grounded in social constructivism and cognitive load theory, the study explains the tension between technological support and reduced learner effort. Using a qualitative descriptive approach, semi-structured interviews were conducted with six experienced teachers. The findings reveal mixed attitudes: while Chat GPT offers valuable language support, teachers expressed concern that overuse weakens critical thinking and encourages cognitive laziness, particularly in writing tasks. The results also highlight a gap between students’ technological skills and schools’ readiness to manage AI use. The study recommends redesigning homework, strengthening classroom-based assessment, and providing AI literacy training to ensure that AI supports learning rather than replacing students’ own efforts.